Theories of change and evaluation of Malaysian rural internet centers - Alias, Nor Aziah; Jamaludin , H.; Ismail, I.S.; Hashim, Sulaiman; Suhaili, N (2010)
The paper describes the findings from the early phase of a research conducted to evaluate the impact of utilization of Malaysian Rural Internet Centers (RICs) on user’s sense of social connectedness and empowerment. It employs a theory of change approach to study the outcomes brought about by the RICs. Initial findings however, suggest that the RICs have evolved individually and are unique from each other, thus requiring a revised evaluation framework based on each RIC’s role and functions. Interviews, observations and document analysis conducted at six RICs imply three main models: (1) The Cyber-café model, (2) The community service center model and (3) The entrepreneurial center model. Three theories of change are subsequently proposed to address each model and further aid the evaluation of the RICs in each category.